Two DLSU faculty delivered lecture - Mendoza, Robeto (Animo Repository, 1997)
Roberto Mendoza of the Psychology Department delivered a paper on "Prostitusyon, pulitika at Pasig: isang pag-aninag sa salitang marumi" during the Pambansang Samahan sa Sikolohiyang Pilipino on the theme "Kapaligiran, kabuhayan at kulturang Pilipino". Simon Lloyd Restubog, Center for Educational Evaluation and Research Director of the DLSU-CSB, was co-author of the lecture.Date of the event was on December 11-14, 1997.